Herausforderungen und Lösungsansätze bei der Diagnostik einer Wurzelquerfraktur im Röntgenbild - Maier, Eva; Holzner, Anna-Louisa; Petschelt, Anselm (Oralprophylaxe und Kinderzahnheilkunde, 2020)
Objectives: Discussion of the importance of X-ray diagnostics in dental traumatology and requirement of multiple X-ray images in different axes for sufficient diagnostics. Clinical procedure: The 11-year-old patient showed up in the emergency unit of the dental clinic in Erlangen in April 2018 around 9 pm, approximately 2 hours after crashing in a slide in a public swimming pool. After detailed examination of the tooth 11 a root-crown-fracture with involvement of the pulp was diagnosed. The fragments of the tooth 11 were partially present but could not be joint together in order to restore the crown. The X-ray taken in occlusal view before emergency treatment did initially not show any abnormalities or fractures. No movement of the crown could be found, the tooth was tender to percussion and did not react to testing of sensibility. Emergency treatment included documentation via photographs and detailed information of the treatment steps: local anaesthesia was followed by a micropulpotomy using calcium hydroxide. Further dentine defects were capped using composite. The patient showed up in the dental clinic the following day complaining about slight pain (regio 11). The tooth was still tender to percussion and not reacting to testing of sensibility. An orthopantomogram for further examination of the temporomandibular joint showed a root fracture in the apical third of tooth 11. This diagnose was confirmed via another small X-ray using a different angle vertical to the tooth axis. The patient and her mother were informed about further treatment options (root canal treatment of the coronal part of the root, MTA plug) and the questionable outcome of tooth 11. Conclusions for practice: In order to perfectly diagnose or exclude root fractures after dental trauma X-rays using different axes should be taken. Also, a high resolution cone beam computed tomography (CBCT) can be considered for further examination in complex cases.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Crown-root-fracture; Dental trauma; Horizontal root fracture; MTA; Pulpotomy; X-ray diagnostics